(untitled) (CIPEEX, 2025)
Postpartum infections are quite common and represent a serious risk to maternal life and health, contributing significantly to the maternal mortality rate, both in Brazil and worldwide. The incidence of these infections is influenced by a series of factors, ranging from the patient’s individual characteristics to the health practices adopted by the institution, making it a significant challenge in maternal health, with profound implications for postpartum recovery. Several risk factors are associated with these infections. The objective of this study is to carry out a literature review to identify the main risk factors associated with hospital-acquired postpartum infections, in addition to evaluating evidence-based prevention and intervention strategies to improve maternal health and the quality of hospital care. This is a narrative-type bibliographic review study. The search will be carried out in the Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific evidence in health in Latin America and the Caribbean (BIREME/OPAS/WHO) and PubMed, in addition to academic repositories and manuals from the Ministry of Health, published in full between 2019 and 2024. This project is of utmost importance for health education, as it seeks to identify the main risk factors, highlight prevention and intervention practices, and point out areas that require more investigation. It is concluded that postpartum hospital infections continue to represent a significant challenge for maternal health, influenced by a complex interaction of individual and institutional risk factors. The identification of these factors is crucial for developing effective prevention and intervention strategies, which can reduce the incidence of these infections and, consequently, maternal mortality. This study highlights the importance of evidence-based health practices and the implementation of public policies that aim to improve the quality of hospital care, aiming to reduce hospital infections in the postpartum period and promote a safer environment for mothers.